Komitmen Bank Syariah Indonesia (BSI) dalam Mendukung Pertumbuhan Sektor Pertanian di Indonesia - Sholihatussifa, Nailis; Utami, Cahyaning Budi; Wahidullah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Badan Pusat Statistik (BPS) The agriculture sector plays an important role in Indonesia's economic development, construction, and trade. As an agricultural country, the agricultural sector can protect natural resources, provide security and welfare, and create jobs. However, the development of Indonesia's agricultural sector faces several obstacles and challenges. This research is a quantitative study where researchers have a strong foundation of information as a scientific result. This research also takes from several data sources such as books and documents, relevant journals, websites to strengthen the author's arguments in conducting this research. The data collection technique used in this research is quantitative data analysis which uses secondary data in the form of annual reports 2021-2023 distributed by PT Bank Syariah Indonesia Tbk. By using Descriptive Data Analysis Techniques and Drawing Conclusions. To obtain this data, it can be obtained from the internet media. It shows that on the contract side, financing in the agricultural sector at BSI is dominated by the Murabahah contract, the second position is the Musyarokah contract, the third is the qordh contract, then the Mudharabah contract. the amount of financing disbursed to the agricultural sector continues to increase from year to year. Currently, the largest financing product at BSI is Murabahah. For the banking industry, this product is a popular product because the transaction is easy to do and does not have a high risk. Murabahah financing is the type of financing that is most widely distributed by Islamic banks to the agricultural sector. BSI has developed various financing products for small and medium enterprises in agriculture, including the BSI Mitra Plasma Sawit program. This financing is dominated by Murabahah contracts, which shows BSI's innovation in Islamic financing schemes.